CORPORATE GOVERNANCE AND QUALITY OF ACCOUNTING INFORMATION IN FAMILY COMPANIES: CORPORATE GOVERNANCE AND QUALITY OF ACCOUNTING INFORMATION IN FAMILY COMPANIES - Gomes, Vanielle Aparecida Patrocinio; Gonçalves, Wellington; Freitas, Rodrigo Randow de; Mattos, Aliomar Lino; Oliveira, Rodrigo Ribeiro; Zatta, Fernando Nascimento (Brazilian Journal of Production Engineering, 2020)
This study aims to use the academic research tool as a basis on the theme “Corporate Governance and Quality of Accounting Information in Family Businesses” using the Web of Science platform highlighting the scientific works already produced on the subject. For this, it used the bibliometric research method, in which the main works and authors are presented by citation criteria, the most discussed themes and theories, the geographical distribution of production, the predominant languages ​​and the evolution and trend of the research. Resulting in a quantitative and qualitative analysis of the studies directed to the keywords that were searched. With the portfolio of two final articles that would contribute in a relevant way to the study, it is possible to see that the governance structure can influence the concentration of ownership, and the concentration, in turn, influences the quality of accounting information.